On the solution of quasilinear elliptic equations by finite-difference method - Sapagovas, M. P. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: М. П. Сапаговас, К вопросу о решении квазилинейных эллиптических уравнений методом конечных разностей M. P. Sapagovas, Kvazitiesinių elipsinio tipo lygčių sprendimo baigtinių skirtumų metodu klausimu